Proceedings. - Symposia on Nuclear Power and Computer Application (Bicutan, Taguig, MM : National Research Council of the Philippines, 1984)
Contents.--Symposium on Nuclear Power as a Source of Energy.--Symposium on Nuclear War and the Doomsday Syndrome in a Developing Society.--Symposium in Computer Applications in Engineering.--Symposium on Nuclear Energy.
Includes references.
Keywords: Nuclear energy -- Philippines -- Congresses; Engineering -- Data processing -- Congresses